The Role of Inner Conflict in Shaping Personality The Case of : Rudolfo Anaya’s Character Antonio in Bless Me, Ultima - BENGUESMIA ,Ikram; ZIANI ,Salima; GUELLIL, Assia (Faculty of Letters and Foreign Languages Department of English, 2019)
The current dissertation seeks to provide an analytical study that aims at exploring the significance of cognitive dissonance in Rudolfo Anaya’s Bless Me, Ultima. To fulfil this aim, reading the novel through the lens of Leon Festinger and Sigmund Freud’s theory about internal conflict would be of a great relevance in explaining the experience of the character in the context of inner conflict. The character, Antonio Marez Lunas is considered a bi-cultural individual, Spanish and Anglo, Catholic and Indigenous beliefs, which both are highlighted in this research. The confrontation between the two sides needs a portal that serves as a middle ground for the growing personality. The portal, this research seeks to demonstrate, is considered as a state of confusion and a continuous moral and psychological conflict. In this regard, the paradoxical socio-cultural aspects Antonio has make an impact on the character’s personality development. At the end, Antonio Marez Lunas becomes able to combine all of his cognitions and dualities to form one fully independent personality